Sebgugugu the glutton : a Bantu tale from Rwanda - Aardema, Verna (W.B. Eerdmans Pub. Co. ; Africa World Press, 1993)
A greedy poor man tests the patience of Imana, Lord of Rwanda, until he loses everything.